The roles of cognitive ergonomics in reducing human error and burnout among emergency room nurses during the Covid-19 pandemic - A.P., Rezki Amelia Aminuddin; Hakim, Hakim (Periodicals of Occupational Safety and Health, 2023)
Background: Mental health, particularly burnout syndrome, is one of the concerns that can influence the productivity of health workers during the pandemic. This is because health professionals are under intense pressure, but there is no guideline or procedure in place to safeguard them in terms of mental health. The objective of this study is to discover burnout and human error, as well as to provide advice, by analyzing the ergonomic factors. Method: Human Error Assessment and Reduction Technique was the identifying approach employed (HEART) in this study. The sample consisted of ten emergency room personnel from one of the hospitals in Yogyakarta. Results: The activity with the greatest HEP was the delivery of first aids, which had a value of 0.068. This activity requires more difficult and complex labor abilities, making human unreliability more significant and increasing the likelihood of human error. Conclusion: Recommendations are made to assist nurses in dealing with heavy and varied workloads so that the reliability of nurses at work can be increased and burnout can be reduced, including the suppression of environmental factors to be as small as possible to reduce the workload of nurses, urging nurses to begin monitoring the situation and taking anticipatory steps so that the burnout does not worsen, and holding regular sharing sessions among nurses, upgrading knowledge and fostering a sense of togetherness.